Biosafety of 3D printed titanium alloy porous materials to osteoblast cell line MC3T3-E1 - JING Li, SHI Wen, CAO Yu, LIU Rui-sai, LIU Lu, LI Jian-yu, LIU Hui (Jichu yixue yu linchuang, 2020)
Objective To prepare 3D-printed porous materials of titanium alloy by electron beaming melting (EBM) and to confirm its biosafety to osteoblasts (OB). Methods Three topological structures of titanium alloy porous materials (2.0 mm, 2.25 mm and 2.5 mm Dode-Medium structure) were prepared by 3D printing technology. The extracts of titanium alloy porous materials were collected at multiple time points (24,48,72,96 h) and used for in vitro culture of osteoblasts cell line MC3T3-E1. The relative growth rate (RGR) of osteoblasts was cal-culated by MTT test. The morphological observation of osteoblasts was performed by HE staining. The activity of ALP was determined for analyzing the differentiate capacity of osteoblasts. The expressional level of Col Ⅰ in osteoblasts was assessed by immunofluorescence staining. Results Following incubation with extracts of titanium alloy porous materials, the osteoblasts were found to adhere and proliferate actively. There was no significant difference in the RGR of osteoblasts between extract group and the negative control group of DMEM. However, the RGR of osteoblasts increased significantly in extract groups compared with that in the positive control group of DMSO (P＜0.01). The cytotoxic degree of osteoblasts in extract groups was all less than or equal to 1. There was no significant difference in the level of ALP and Col Ⅰ of osteoblasts between extract groups and the negative control group of DMEM. However, the level of ALP and Col Ⅰ of osteoblasts enhanced significantly in extract groups compared with that in the positive control group of DMSO (P＜0.01). Conclusions The extracts of titanium alloy materials do not affect the proliferation and differentiation of osteoblasts in vitro that confirmed its biosafety.